Remission of Refractory Benign Familial Chronic Pemphigus (Hailey-Hailey Disease) with the Addition of Systemic Cyclosporine. Issue 2 (March 2015) - Varada, Sowmya; Ramirez-Fort, Marigdalia K.; Argobi, Yahya; Simkin, A. David
Background: Benign chronic familial pemphigus (BFCP) is an autosomal dominant dermatosis characterized by flares of painful and often debilitating blistering lesions in high friction areas of the body such as the groin, axillae, lateral neck, and intergluteal cleft. Limited knowledge of its pathophysiology has made treatment of BFCP a considerable challenge and efficacy with current first line therapies, topical corticosteroids and antibiotics, is variable. Case Report: We present a case of this disease in a 52 year old woman that has responded dramatically to the addition of oral cyclosporine to her existing regimen of oral acitretin, with significant improvement of skin lesions, mobility, and quality of life. Cyclosporine's mechanism of action in BFCP is poorly understood, although it possibly acts through inhibition of proinflammatory cytokines in keratinocytes or modulation of intracellular calcium. BFCP, the use of cyclosporine for its treatment, and possible mechanisms of action of cyclosporine are reviewed.